Novel Mouse Model for Studying Hemostatic Function of Human Platelets. Issue 8 (August 2020) - Paul, David S.; Bergmeier, Wolfgang
Abstract : Objective: Platelets are critical to the formation of a hemostatic plug and the pathogenesis of atherothrombosis. Preclinical animal models, especially the mouse, provide an important platform to assess the efficacy and safety of antiplatelet drugs. However, these studies are limited by inherent differences between human and mouse platelets and the species-selectivity of many drugs. To circumvent these limitations, we developed a new protocol for the adoptive transfer of human platelets into thrombocytopenic nonobese diabetic/severe combined immune deficiency mice, that is, a model where all endogenous platelets are replaced by human platelets in mice accepting xenogeneic tissues. Approach and Results: To demonstrate the power of this new model, we visualized and quantified hemostatic plug formation and stability by intravital spinning disk confocal microscopy following laser ablation injury to the saphenous vein. Integrin αIIb β3 -dependent hemostatic platelet plug formation was achieved within ≈30 seconds after laser ablation injury in humanized platelet mice. Pretreatment of mice with standard dual antiplatelet therapy (Aspirin+Ticagrelor) or PAR1 inhibitor, L-003959712 (an analog of vorapaxar), mildly prolonged the bleeding time and significantly reduced platelet adhesion to the site of injury. Consistent with findings from clinical trials, inhibition of PAR1 in combination with dual antiplatelet therapy markedly prolonged bleeding time in humanized platelet mice. Conclusions: We propose that this novel mouse model will provide a robust platform to test and predict the safety and efficacy of experimental antiplatelet drugs and to characterize the hemostatic function of synthetic, stored and patient platelets. Abstract : Supplemental Digital Content is available in the text.